387 CARCINOMA ERYSIPELATOIDES ASSOCIATED WITH DIFFUSE LARGE B-CELL LYMPHOMA. Issue 1 (1st January 2007) - Khan, B. Q.; Gandhi, M.; Edmonds, H.; Ahmad, K.; Rasberry, R. D.; Corbett, C. E.; Jukkola, A. F.; Carbone, L. C.
Abstract : Purpose: The purpose of this study is to describe a case of carcinoma erysipelatoides occurring in association with diffuse large B-cell lymphoma (DLBCL). Material and Methods: Case study including medical history, physical examination, laboratory and radiographic reports of a 64-year-old Caucasian male with a history of a nonhealing, erythematous, indurate plaque-like rash (20 × 32.5 cm) over his abdomen. Results: Laboratory studies were significant for leukopenia (WBC 2.2/mm 3 ), with a negative CT and ultrasonography of the abdomen and pelvis for any abcess. Initially, the patient was diagnosed with cellulitis and treated with antibiotics; however, blood cultures remained negative, and there was no improvement in the skin lesion. Subsequent punch biopsy was consistent with tumor cells similar in morphology and immunochemical staining to the original DLBCL. Antibiotics were discontinued; the patient was discharged home and expired shortly thereafter. Conclusion: Although cases of carcinoma erysipelatoides occurring in association with solid tumors have rarely been described, to our knowledge, this is the first report of carcinoma erysipelatoides occurring in association with a hematologic malignancy. The treating physician needs to consider carcinoma erysipelatoides in the differential diagnosis of nonhealing rashes that resemble cellulitis in patients with lymphoma.